2016
DOI: 10.1071/mf15032
|View full text |Cite
|
Sign up to set email alerts
|

Daily growth patterns of juveniles and adults of the Peruvian anchovy (Engraulis ringens) in northern Chile

Abstract: Abstract. The Peruvian anchovy (Engraulis ringens) is a resource of considerable economic importance, whose stock unit is distributed between 16800 0 S and 24800 0 S and is shared between Chile and Peru. In the present study, daily growth patterns of juvenile and adult Peruvian anchovies in northern Chile were determined using micro-increments of sagittal otoliths for the recruitment and fishery seasons of 2009 and 2010. A characteristic feature was the existence of very distinctive daily micro-increments, thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 60 publications
2
17
0
Order By: Relevance
“…In the case of the pre‐recruits, the age–length relationship showed a substantive increase in growth rate relative to the larval period, with maximum growth rates of c. 0.9 mm d −1 reached between the 30th and 70th days, supporting the results reported by Cerna and Plaza (). They demonstrated that most growth variability in E. ringens occurred during the first month of life.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In the case of the pre‐recruits, the age–length relationship showed a substantive increase in growth rate relative to the larval period, with maximum growth rates of c. 0.9 mm d −1 reached between the 30th and 70th days, supporting the results reported by Cerna and Plaza (). They demonstrated that most growth variability in E. ringens occurred during the first month of life.…”
Section: Discussionsupporting
confidence: 88%
“…The results derived from the interannual analysis of age at recruitment showed that, irrespective of year and season, juveniles typically recruit to the fisheries around 5 months after hatching, which provides further evidence of the fast growth of this species during its first year of life. Under a fast‐growth scenario, a large fraction of the asymptotic length can probably be reached within only a few months of life and consequently, the year‐class strength will be a product of the survival rates from just one season before and could have great relevance for the management of the anchovy fishery (Cerna & Plaza, ). The new scenario of accelerated growth in anchoveta reduces the time required to reach sexual maturity by half ( i.e.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In short-lived species, such as small pelagic fishes, particular effort has been devoted to understanding the growth-mortality mechanism as it is considered the most important driver of recruitment variability of sardine and anchovy stocks (e.g., Jacobson & MacCall, 1995;Sinovčić, 1998;Allain et al, 2001;La Mesa et al, 2009;Schismenou et al 2014). On the contrary, only few studies have focused on the growth of adults, underlining the importance of growth on biomass production of populations (Van Beveren et al, 2014;Cerna & Plaza, 2016;Uriarte et al, 2016).…”
Section: Introductionmentioning
confidence: 99%